Citotoxicidade transamelodentinária de uma fita clareadora com 10% de peróxido de hidrogênio sobre células de linhagem odontoblástica - Pontes, Elaine C.V. [UNESP]; Gomes, Livia R. M.; Soares, Diana Gabriela de Souza [UNESP]; Ribeiro, Ana Paula Dias [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (My University, 2012)
To evaluate the cytotoxicity of a whitestrip (WS) with 10% hydrogen peroxide (HP) on cultured odontoblast-like cells. Material and Methods: Enamel/dentin discs were adapted to artificial pulp chambers and placed in wells with culture medium (DMEM). The WS was applied on enamel for 60 min (2 x 30 min) during 1 or 5 days. The extracts (DMEM + WS components that diffused across enamel and dentin) were applied to the cells for 1 h. In the positive control, the bleaching gel with 35% HP was applied for 45 min (3 x 15 min). In the negative control, no treatment was performed. The cell metabolism (MTT Assay) and alkaline phosphatase (ALP) activity were assessed and the data submitted to statistical analysis (One-way Anova/ Tukey’s test; α=5%;). Cell membrane damage was evaluated by flow cytometry. Results: For the MTT and ALP activity assays, there was no significant difference among the bleached groups with WS and negative control, regardless the time of WS application (1 or 5 days) on the cells (p>0.05). However, there was no significant difference among the bleached group with FC for 5 days and positive control. Flow cytometry analysis showed an increase of cell membrane damage only for the positive control. Conclusion: It was concluded that the whitestrip with 10% of HP did not cause significant trans-enamel and trans-dentinal toxic effects to the MDPC-23 cells.

Avaliar a citotoxicidade trans-amelodentinária de uma fita clareadora (FC) com 10% de peróxido de hidrogênio (PH) sobre células odontoblastóides MDPC-23. Material e Método: Discos de esmalte/dentina adaptados em câmaras pulpares artificiais foram posicionados em compartimentos contendo meio de cultura (DMEM), sendo o esmalte submetido a 2 aplicações de 30 minutos da FC. O meio de cultura em contato com a dentina (extrato) foi aplicado sobre as células por 1 hora, durante os períodos de 1 ou 5 dias. Como controle positivo, foram realizadas 3 aplicações de 15 min de um gel clareador com 35% de PH. No grupo controle negativo, nenhum tratamento foi realizado no esmalte. Após os períodos de avaliação, as células MDPC-23 foram analisadas quanto ao metabolismo (Teste de MTT), atividade da fosfatase alcalina (ALP) (Anova e Tukey; α=5%;) e danos à membrana celular (citometria de fluxo). Resultados: Quanto ao metabolismo e atividade de ALP, não houve diferença significante entre os grupos clareados com a FC e o controle negativo, independente do número de aplicações do extrato sobre as células (p>0,05). Porém, o grupo clareado com a FC por 5 dias também não foi diferente estatisticamente do controle positivo. A análise por citometria de fluxo indicou danos à membrana celular para o grupo controle positivo. Conclusões: Concluiu-se que a FC com 10% de PH não causou efeito tóxico significante para as células MDPC-23; porém, o aumento na freqüência de aplicação pode vir acompanhado de maiores efeitos tóxicos para as células em cultura.
Trans-enamel and trans-dentinal cytotoxicity of a 10% hydrogen peroxide whitestrip on odontoblast-like cells
Keywords: Tooth bleaching; Toxicity; Odontoblasts; Clareamento dental; Toxicidade; Odontoblastos